What does individual strength say about resistance training status?. Issue 4 (9th January 2017) - Buckner, Samuel L.; Mouser, J. Grant; Jessee, Matthew B.; Dankel, Scott J.; Mattocks, Kevin T.; Loenneke, Jeremy P.
ABSTRACT: The point at which an individual becomes resistance "trained" is not well defined in the literature. Some studies have defined training status as having engaged in consistent resistance training activities for a given period of time, whereas others base inclusion criteria on strength levels alone, or levels of strength in combination with training age/time. If the primary focus of a study is to examine adaptations in individuals with high levels of strength, then it may be appropriate to exclude the individuals who do not meet strength requirements. However, given the heterogeneity of the strength response to resistance training, strength cannot separate those who are "trained" from those who are "untrained." We suggest that, when determining resistance training status, training age (time) and the modality of training (specificity) should be the primary criteria considered. Muscle Nerve 55 : 455–457, 2017